Infiltration Well Design for Environmental Conservation: Assessing Watershed and Groundwater Depth in Denpasar City - Pamungkas, Tri Hayatining; Yekti, Mawiti Infantri; Ardana, Putu Doddy Heka; Warsana, Kadek Budhi; Kembarajaya, I Ketut (Universitas Diponegoro, 2025)
Urbanization and climate change are expected to exacerbate and introduce uncertainty in future flood characteristics. The city of Denpasar often experiences flooding due to rapid population growth and changes in land use. One form of flood mitigation that can be implemented is infiltration wells. This research aims to design infiltration wells as an environmental conservation effort by evaluating the characteristics of the watershed and the depth of groundwater. This research will also examine lithological aspects and use geographic information systems (GIS) to increase effectiveness in planning. The research results show that the construction of infiltration wells at the research location is effective in reducing flood volume, with reductions varying between 19.86% in South Denpasar and 59.58% in North Denpasar, East Denpasar and West Denpasar. Infiltration wells not only reduce the risk of flooding but also play an important role in preserving the environment according to the Tri Hita Karana concept. By integrating these sustainable practices into spatial planning, water resource management can be enhanced, fostering a healthy environment for future generations.